Análise numérico-experimental da minimização da formação de gelo poroso em placas planas - Biglia, Felipe Mercês (2018)
This Master's Dissertion comprises a numerical-experimental analysis of frost formation on flat plates with different surface treatments. This phenomenon occurs when the flow of the air and water vapour mixture comes into contact with surfaces that have temperatures below 0ºC, present in several commercial and industrial applications that reach low temperatures, going directly to the solid state (phase transition by resublimation), giving rise to a porous structure, organized by irregular crystals of ice. It's accumulation implies in the increase of energy demand and decrease in the performance of several equipment involved in the refrigeration process, reducing your efficiency and making necessary a periodic withdrawal, resulting in expenses. In this context, an experimental apparatus of low cost was developed, allowing an experimental analysis of the phenomenon under study. The environmental conditions evaluated are the plate surface temperature, ambient temperature, humidity and air velocity. The material of the surfaces under study are aluminum, copper and brass with different surface finishes, designated as: smooth, grooved (hydrophilic) and varnished (hydrophobic). The numericalexperimental analysis demonstrates measurements and simulations of the thickness, surface temperature and deposition velocity of the frost by elapsed time. The numerical results had good agreement with the experimental results, indicating that the varnished surface, with hydrophobic characteristics, presents greater difficulty in providing the phenomenon.